Pengaruh Corporate Social Responsibility dan Good Corporate Governance Terhadap Earnings Management - Ai Hendriani; Della Sabela (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyze the effect of CSR and GCG on Earnings Management in oil and gas sector mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. The results showed that CSR has a positive influence on earnings management, indicating the importance of social integrity and corpo- rate responsibility towards society and the environment. On the other side, unex- pected findings are related to GCG, which was previously assumed to have a neg- ative influence on earnings management. However, the results showed that GCG also has a positive influence on Earnings Management, contrary to the previous hypothesis. This study used a sample of 7 companies or 35 company data that met the criteria over a span of 5 years (2018-2022), with the sampling technique used was purposive sampling method. However, this research only examines one com- pany sector. Further research is needed by adding data variables and expanding the company sample, so as to provide a more comprehensive understanding of CSR, GCG and earnings management. Keywords: Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), Earnings Management.